Maxillary sinus residual root removal: Modified Caldwell-Luc technique (Research, Society and Development, 2024)
Tooth extractions are dental procedures routinely performed in dental clinical practice, and in many cases, we find close contact between the roots of the upper teeth and the maxillary sinus. This anatomical structure contributes to making the viscerocranium lighter, playing a crucial role in the respiratory system, heating the inspired air and contributing to vocal resonance. Due to its proximity to the upper teeth, various pathological and iatrogenic complications can occur during tooth extractions, requiring surgical interventions to be resolved. Among the surgical procedures, the modified Caldwell-Luc technique enables the removal of foreign bodies from the maxillary sinus, detailed inspection, ease of execution, and great effectiveness. The aim of this study is to report a clinical case in which the successful removal of a root remnant from the maxillary sinus using the modified Caldwell-Luc technique was performed, highlighting the importance of the procedure in contemporary surgical practice. It is concluded that the presence of foreign bodies in the maxillary sinus should be immediately addressed, with the modified Caldwell-Luc surgical approach being an excellent choice for resolving these cases, avoiding the emergence of local and systemic infectious conditions.